Development of functional thermoplastic polyurethane nanocomposites via selective laser sintering - Zhou, Meixin (Nanyang Technological University, 2023)
Selective laser sintering (SLS) has attracted tremendous attention in fabricating polymer parts for aerospace, automotive, and biomedical applications. Its unique advantages, including the ability to fabricate integrated structures, produce multiple parts during a single printing process, and eliminate the post-processing labor of removing supporting structures, make it a cost-effective and efficient method for fabricating complex and integrated structures. However, the application of SLS has been limited by a scarcity of available material feedstock options. Among emerging materials, thermoplastic polyurethane (TPU) nanocomposites have shown great promise due to their versatile properties, such as excellent energy absorption capability, high flexibility, and shape memory properties. Nevertheless, the development of functional TPU nanocomposite powders specifically designed for the SLS process remains inadequate. Moreover, a poor understanding of the process−microstructure−property relationship for the SLS process, the limited functionality of the existing TPU-based materials, and the lack of engineering designs for SLS-printed parts hamper the development of the SLS of TPU-based materials. Therefore, this thesis aims to systematically develop functional TPU-based nanocomposite powders for the SLS process, investigate the effects of functional fillers on the SLS process, and design structures for potential applications. An in-depth investigation of the SLS of neat TPU powders is fundamental to the development of functional TPU-based nanocomposites. Aromatic and aliphatic TPU powders were compared in terms of their SLS processability, microstructure, and mechanical properties to illustrate the influence of the chemical structure of TPUs in the SLS process. The pores within the parts printed under different process parameters were classified into lack-of-fusion pores, gas pores, and interlayer voids according to their morphological features, and the former two types of pores were found to be detrimental to the mechanical properties of the printed parts. The origin of pores of each type was revealed to guide the optimization of the SLS process for achieving minimal porosity. Novel triple periodic minimal surface structures were designed and fabricated into customized footwear to utilize their features of high mechanical energy absorption and adjustable mechanical properties. In light of the high stretchability of TPU, electrically conductive TPU-based nanocomposites were developed for applications in wearable strain-sensing devices. The nanocomposite powders were developed by coating the surface of the TPU particles with carbon nanotubes (CNTs) via the latex technology. It was found that with the increase in the CNT content, the SLS processability and mechanical properties degraded, as reflected by the reduced powder flowability, increased melt viscosity, and decreased ultimate tensile strength. However, the electrical and piezoresistive properties were enhanced because of the increase in the number of conductive paths. A mathematical model was established based on the tunnelling theory to predict the piezoresistive response of the developed materials. The developed 2.0 wt% CNT/TPU nanocomposites exhibited a high piezoresistive sensitivity with a gauge factor of 60 at a strain of 20% and maintained stable performance after 100 loading-unloading cycles. A two-dimensional (2D) chiral structure with a J-shaped stress‒strain curve during the tensile process was designed to enhance the conformability, and a wearable ring with the designed 2D chiral structure was fabricated to illustrate the potential role of such conductive nanocomposites in wearable strain-sensing devices. Stimuli-responsive TPU-based nanocomposites were developed for applications in remotely controlled smart components by leveraging the shape memory properties of TPU. The functional nanocomposite powders were developed by mechanically mixing a designed multiscale hybrid filler with the CNT−coated TPU powders. The multiscale hybrid filler was prepared by grafting hydroxylated CNTs on plasma-treated carbon fibers (CFs) with isocyanates as the bridge. The shape recovery process of the nanocomposites with a 20 wt% hybrid filler addition was almost four times faster and exhibited a higher shape recovery ratio when triggered by electric currents than those triggered by the direct heating method. The underlying mechanism behind the electro-activated shape memory behaviors of the printed nanocomposites was also revealed, providing insights into the development of shape memory nanocomposites via SLS. Moreover, a smart four-dimensional architecture was fabricated to demonstrate their potential applications in remotely controlled smart components for soft robotics. This thesis presents a complete workflow involving the material design, process optimization, structural design, and corresponding applications of the SLS technique for TPU-based materials and establishes a systematic protocol for the development and evaluation of functional TPU-based nanocomposite powders for the SLS process. Additionally, the effect of the functional fillers on the process−microstructure−property relationship is thoroughly revealed, which could provide profound insights into the design of functional materials for the SLS process.